Analisis Pemahaman Peraturan Permainan Sepak Bola Melalui Video Test pada Wasit Askot PSSI Surakarta - Muh. Isna Nurdin Wibisana; Husnul Hadi; Setiyawan Setiyawan; Nur Azis Rohmansyah (YLPK Mahardhika, 2022)
The COVID-19 pandemic since the beginning of 2020 forced all PSSI calendar matches to be suspended until mid-2021. The referee will feel the same way, the lack of minutes in leading the match will greatly affect the feeling-touch in making decisions. This problem became a consideration for the research team to analyze the understanding of football regulation through a video test on the Surakarta City PSSI Askot referee. The use of the video test is intended to refresh the ability of the referees, especially the PSSI Surakarta City Askot referee in understanding the rules of the football game because it is still a pandemic condition and there are no official matches being held, so when the competition rolls the referees are ready to lead the match. This research is a quantitative descriptive study that aims to analyze the understanding of soccer game rules through a video test on the ASkot PSSI Surakarta referee. The population in this study is the ASkot PSSI referee in Surakarta. The sampling technique used is saturated sampling, that is, all referees at the PSSI Askot Surakarta City starting from licenses C3, C2, and C1 will be used as research samples. analysis technique that can be used is to use the frequency distribution technique. The results of the research for the referee's understanding of offside illustrate that 7 people are in the low category or 35%, 7 people are in the medium category, or 35%, and 6 people are in the high category, or 30%. The referee's understanding of handball is that 10 people are in the medium category or 50%, and 10 people are in the high category or 50%. The conclusion of this study is that the understanding of offside is still low, this is related to the feeling-touch that has not fully returned to its best performance. There needs to be practice and treatment to restore feeling-touch and make the right decisions.